THE RELATIONSHIP BETWEEN FINANCIAL LITERACY AND SAVINGS BEHAVIOR AMONG JAKARTA COLLEGE STUDENTS IN THE DIGITAL AGE: HUBUNGAN ANTARA LITERASI KEUANGAN DAN PERILAKU MENABUNG DI KALANGAN MAHASISWA JAKARTA PADA ERA DIGITAL - Maghfirah Wadiah; Ahmad Faishal Zindan; Asiroch Yulia Agustina (JASIE, 2025)
This study aims to examine the relationship between financial literacy and saving behavior among university students in Jakarta in the digital era. A quantitative associative approach was employed using purposive sampling technique, involving 60 active students from various universities in Jakarta who hold savings accounts or use digital financial products. Data were collected through a structured questionnaire distributed via Google Form and analyzed using descriptive statistics. The results show that students’ financial literacy is at a moderate to high level in conceptual aspects, such as distinguishing needs from wants, recording financial transactions, and recognizing online fraud. However, technical literacy particularly the ability to calculate interest and understand banking terminology remains relatively low. In terms of saving behavior, most students demonstrate a positive orientation toward saving, with clear goals and reasonable consistency. Conventional bank accounts remain the primary medium for saving, although the use of digital wallets is growing. There is strong evidence that financial literacy is positively correlated with saving behavior; students with higher financial literacy tend to save in a more planned, disciplined, and digitally adaptive manner. This study recommends integrating digital-based financial literacy education into university curricula to cultivate a financially literate younger generation.